Implementasi Manajemen Sekolah Berbasis Kearifan Lokal - Sodiq, Akhmad; Rokhmad, Rokhmad; Furoidah, Aniq Jihan; Nurkholis, Nurkholis (Cetta: Jurnal Ilmu Pendidikan, 2025)
Education is a fundamental pillar in shaping national life, where schools play a strategic role in the holistic development of students' character and potential. In the era of globalization, innovation in school management is necessary to make education more adaptive. One innovative approach is school management based on local wisdom, which integrates values, traditions, and cultural practices into the management process. This study aims to explore the implementation, potential, and challenges of this approach and to formulate recommendations for its development. The research was conducted at SD N 1 Kebonharjo, Kendal Regency, focusing on the preparation of strategic plans that integrate local values and culture. The results show that values such as mutual cooperation (gotong royong), deliberation (musyawarah), and the utilization of local resources strengthen school management and improve education quality. However, challenges such as deep understanding and limited resources need to be addressed. This study contributes to academics, practitioners, and policymakers in strengthening cultural identity and education quality through school management based on local wisdom, emphasizing character building and patriotism.